2015
DOI: 10.1111/phpp.12180
|View full text |Cite
|
Sign up to set email alerts
|

Ex vivo evaluation of the effect of photodynamic therapy on skin scars and striae distensae

Abstract: Using our unique ex vivo model, we show for the first time morphological and cellular effect of application of PDT, which correlates with the degree and severity of dermal fibrosis. In view of this, PDT may be ideal in targeting treatment of abnormal skin scarring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 39 publications
(60 reference statements)
1
21
0
Order By: Relevance
“…A further ex vivo study utilised an organ culture model of dermal fibrosis to investigate the effect of photodynamic therapy on skin scars and stretch marks in humans . This unique ex vivo model showed the morphological and cellular effect of photodynamic therapy and correlated this with the degree and severity of dermal fibrosis.…”
Section: Resultsmentioning
confidence: 99%
“…A further ex vivo study utilised an organ culture model of dermal fibrosis to investigate the effect of photodynamic therapy on skin scars and stretch marks in humans . This unique ex vivo model showed the morphological and cellular effect of photodynamic therapy and correlated this with the degree and severity of dermal fibrosis.…”
Section: Resultsmentioning
confidence: 99%
“…Sakamoto et al reported that surgical scar remodeling could be achieved by PDT, which indicated that PDT may be effective in the treatment of existing scars . Mendoza‐Garcia et al showed that PDT exposure was associated with decreased levels of collagen and increased levels of MMP3 and elastin in skin scars . He also reported that PDT was associated with increased skin wound healing and increased expression of collagen and MMP3 .…”
Section: Discussionmentioning
confidence: 99%
“…Currently, there is limited consensus on the mechanism of PDT's effects on ECM during scar formation. Mendoza‐Garcia et al reported that PDT was associated with decreased collagen expression in skin scars and increased collagen expression during skin wound healing . Byun et al reported opposite levels of transforming growth factor β‐1 (TGF‐β1) in cultured fibroblasts and keratinocytes following PDT .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the center of these circular skin explants, a 3 mm diameter circular excisional artificial wound was created to a depth of 2 mm by a further punch biopsy. Explants were submerged into sterile 24‐well Corning Costar cell culture plates (Sigma‐Aldrich, Poole, UK), with each well containing 0.5 ml serum‐free Williams E culture medium (ThermoFisher Scientific, Basingstoke, UK) supplemented with 1% (v/v) nonessential amino acid solution, 10 μl/ml insulin, 10 ng/ml hydrocortisone and 2 mmol l ‐glutamine . Explants were maintained at 37 °C in a stationary carbon dioxide (5%) incubator and were cultured for a minimum of 24 hours with daily medium change prior to use and were not utilized beyond 7 days to maintain explant viability …”
Section: Methodsmentioning
confidence: 99%